MARTABAT DALAM ITS WAVERING IMAGE KARYA PENULIS PEREMPUAN CHINA-AMERIKA, SUI SIN FAR - Juliasih Kusharyanto (Universitas Gadjah Mada, 2014)
Multicultural society in the United States is depicted as a mosaic, composed of a variety of races andethnic groups that have always been different from one another. Some people argue that multiculturalismmay undermine solidarity. The designation African-American, Native-American, Asian-American,Hispanic-American, and many more to certain groups of people in a society may cause hostility oreven disintegration. Sui Sin Far in Its Wavering Image expresses her dissenting opinions. She whosupports diversity which is the main issue in America asserts that cultural differences have alwaysexisted. A person can be an American and can still be able to maintain another cultural identity. Shebelieves that all human beings are born free and are equal in dignity and rights. Thus, those who livein a heterogeneous society can be considered as a dignified society. Multicultural feminism theory isapplied to identify the inequalities induced by cultural, racial, ethnic, and sexual diversity.